Sport safety improvement using security camera without audience privacy violation - Suriya Praditsathaporn; Somkuan Kaviya; Preecha P. Yupapin (My University, 2010)
Crime in the sport stadium is an unacceptable situation. It is necessary to watch and inform to the related person. The existed system to date is not replied such a requirement. In this paper, we propose the use of today information technology for crime in watching and investigation in the sport stadium. The system known as wireless-touch screen that uses for sport stadium surveillance, detection, and prevention criminality. It is cheap and movable instrument which is suitable for portable application. The additional system for privacy protection using the camera with angle sensor and spectator's information is also proposed.
Keywords: Stadium; Security system; Sport and Mega-Event Impacts